ANALISIS PENGEMBANGAN BAKAT KHUSUS PADA SISWA KELAS X MADRASAH ALIYAH NEGERI 2 PONTIANAK - Susilawati, Rahmi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Talent is a potential that still needs to be developed, but please note before developing the talent so that distribution in accordance with the special talent possessed first must know what special talents that exist within the individual. However, based on the background of the students, there are still students of class X Madrasah Aliyah Negeri 2 Pontianak who do not know their own talent and how to develop it. This research method used the descriptive method with the survey form. Problem-solving procedure by describing the distribution of Special Talent Development Analysis In Grade X Madrasah Aliyah Negeri 2 Pontianak. Total population 274 and the number of samples 74 taken 25% of the population by random sampling technique. While the data collection techniques used are direct communication techniques and indirect communication. The data collection tools used are interviews and special talent development questionnaires. Based on the results of research processing and data analysis has been implemented, it can be concluded that in general the development of talented students class X madrasah Aliyah 2 Pontianak country was good. Keywords: Special Talent Development